Globalisation and gender : changing patterns of women's employment in Bangladesh - Sobhan, Rehman; Khundker, Nasreen; Centre for Policy Dialogue (Bangladesh) (Dhaka : University Press, 2001)
Contributed articles.
"Centre for Policy Dialogue."
Includes bibliographical references and index.
Keywords: Women -- Employment -- Bangladesh; Occupational training for women -- Bangladesh; Women in rural development -- Bangladesh; Globalization